Analisis Pengaruh Thin Capitalization, Debt Covenant, dan Tunneling Incentive terhadap Transfer Pricing dengan Komite Audit Sebagai Variabel Moderating - Yuana Khoirunisa; Agus Wahyudin (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2022)
This study aims to analyze the effect of thin capitalization, debt covenants, and tunneling incentives on transfer pricing with the audit committee as the moderating variable. The population used is manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019, totaling 170 companies. The data analysis method used is moderated analysis regression with the IBM SPSS 24 tool. The result show that thin capitalization has a significant positive effect on transfer pricing, debt covenants have no significant effect on transfer pricing, and tunneling incentives have no effect on transfer pricing. The audit committee was unable to significantly moderate the relationship between thin capatalization and transfer pricing and was also unable to significanlty moderate the relationship between debt covenants and tranfer pricing, however, the audit committee was able to strengthen the relationship between tunneling incentives and transfer pricing.